STATE OF THE ART: SUSTAINABILITY, URBAN DEVELOPMENT, AND SDG 11, A CRITICAL ANALYSIS IN LIGHT OF GOIÂNIA-GO (CIPEEX, 2026)
One of the United Nations Sustainable Development Goals (SDGs) is the development of sustainable cities, included in SDG 11. This study analyzes the urban planning policies of Goiânia, initially designed for 50,000 inhabitants, comparing them with the SDG 11 targets and their historical conceptual precedents. The research adopts a critical integrative review, with theoretical support from Bardin (2011). We use Mendeley Reference Manager and PRISMA (2020) tools adapted for qualitative research. The adopted databases are multidisciplinary: Google Scholar and Web of Science; and Science Direct and Scielo, focusing on Social Sciences/Urbanism. We observe that the history of Goiânia, Goiás, reveals conflicts between the ideals of modernity and progress of its founding, and unplanned horizontal urban expansion. Comparing Goiânia's historical model with the current principles of SDG 11, there is evidence that its project does not align with SDG 11 targets and has distanced itself from social, environmental, and participatory sustainability.
Keywords: Sustainability; Sustainability; Development; Development; SDG 11; SDG 11; Goiânia-GO; Goiânia-GO